Management of Gender-Based Production and Commercial Spaces - Murtini, Titien Woro; Harani, Arnis Rochma; Adiyati, Arlina (Jurnal Teknik Sipil dan Perencanaan, 2018)
Currently, home industry is attaining particular attention from Indonesian government. This activity is considered as an embryo of Indonesia's economic growth. One of the home industries that have been recognized worldwide is batik. Batik is the cultural heritage of Indonesia that which has received international recognition. The famous batik in Indonesia comes from Pekalongan. In Pekalongan, some villages have characteristic of batik, one of them is proto village. In this village, batik is growing through the home industry business, and almost 70% women can write batik. Also, almost all the houses in this village become a place for industry, whether to make batik, sell batik, and modify batik fabric into clothing. The house which should be a residence, it is functioned as a production and business space. This research employed qualitative method with phenomenology paradigm, aimed to understand and reveal the meaning of the phenomenon of human life behavior, both human in capacity as individuals, groups and the wider community in using residential as a business space and production in Proto Batik Village. The results of this study found that the spatial management system in Proto Batik Village is dominated by women in every home. If the living room in business space used as a place to sell and marketing, the function of production room is located in women area such as kitchens, and backyard. It can be concluded that private house spaces are still used as residential functions, but semi-public spaces are utilized as production and business space.